Green approaches and separation techniques for the recovery of pigments from microalgae - Khoo, Kuan Shiong (2021)
Microalgae have provided great exploitation of biofuels and bioproducts production over fossil fuels and other plant-based sources owing to its high accessibility, non-competition, and renewability advantages. The production of natural carotenoids from microalgae are safer than petrochemical feedstock due to the inherent toxicity concerns for direct human consumption. However, the recalcitrant structure of microalgae cell wall restricted the direct recovery and extraction of the carotenoids accumulated inside the biomass which requires an additional pretreatment process. The current conventional technologies (e.g. bead beating, homogenizers, high pressure heating and chemicals) of biomass processing are incompetent and not feasible for the downstream processing of microalgae. This creates an opportunity of developing novel bioprocessing approaches to reduce the overall cost- and time processing and enhance the efficient production of carotenoids.